Prevalence of occupational infectious diseases among primary oral health care teams and prevention measures - Vargas, Sheila Cristina (Rev Bras Med Trab, 2020)
BACKGROUND: The dental surgeon and dental health assistant experience risk situations and must be prepared for the prevention of diseases and accidents at work. OBJECTIVE: Evaluating the prevalence of occupational infectious diseases and prevention measures used by the DS and dental health assistants. METHODS: Cross-sectional study carried out with professionals working at the Northwestern region of Rio Grande do Sul. We carried out an interview using a structured questionnaire containing variables related to sociodemographic factors and prevention of infectious diseases. Subjects were submitted to blood collection for serological test for infectious diseases. RESULTS: The use of goggles and cap was higher among the dental health assistant. The dental surgeon reported frequent use of mask: 45.5% replaced the used mask at each new patient. All participants reported using gloves and changing them for each new patient. 78.3% of workers have attended patients with infectious diseases. Among professionals evaluated, dental surgeons reported the highest number of accidents with needle stick instruments (59.1%). Post-exposure prophylaxis procedures are known by 68.2% of dental surgeon and 62.5% of dental health assistant. We did not find positive results for hepatitis B, hepatitis C and human immunodeficiency virus (HIV). CONCLUSIONS: We did not found cases of occupational infectious disease. Dental professionals adopt some preventive actions, but a few professionals, even knowing about the risks they will be exposed during work, do not use some protective equipment.